2011
DOI: 10.1111/j.1538-7836.2011.04270.x
|View full text |Cite
|
Sign up to set email alerts
|

ISTH overt disseminated intravascular coagulation score in patients with septic shock: automated immunoturbidimetric soluble fibrin assay vs. D‐dimer assay

Abstract: To cite this article: Gris JC, Faillie JL, Cochery-Nouvellon É , Lissalde-Lavigne G, Lefrant JY. ISTH overt DIC score in patients with septic shock: automated immunoturbidimetric soluble fibrin assay vs. D-dimer assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…Hyperfibrinolysis is frequently seen in hematological malignancies, so choosing a marker which could distinguish secondary hyperfibrinolysis from primary hyperfibrinolysis is more meaningful. In a meta-analysis the area under the ROC was calculated and it was found that D-dimer has a greater area under the ROC than FDP for the diagnosis of DIC [13,14]. Third, APTT was added to the CDSS with the belief that it would improve the diagnostic sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperfibrinolysis is frequently seen in hematological malignancies, so choosing a marker which could distinguish secondary hyperfibrinolysis from primary hyperfibrinolysis is more meaningful. In a meta-analysis the area under the ROC was calculated and it was found that D-dimer has a greater area under the ROC than FDP for the diagnosis of DIC [13,14]. Third, APTT was added to the CDSS with the belief that it would improve the diagnostic sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, a scoring system for overt DIC was proposed by the ISTH, using which overt DIC can be diagnosed in 25% in patients with sepsis [15,16]. However, these diagnostic algorithms remain far from gold standard [17,18]. …”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] The negative predictive value was high in all groups (>87%), indicating the correlation of D-dimer assay and DIC as demonstrated in previous studies. 10,11 Nevertheless, it remains a challenge to optimize D-dimer assays to have a clinical significance for individual patients.…”
Section: Discussionmentioning
confidence: 99%